PENGARUH MANAJEMEN LABA TERHADAP RASIO KEUANGAN PRODUK INDUSTRI KREATIF KERAMIK - Normal, I Nyoman (Jurnal Keuangan dan Perbankan, 2015)
The aims of this research is determine the influence of earning management to financial ratio ceramics creative industry product. The research results shew that the earning management that applied by over production can increase financial ratio ceramics creative industry product, that is : a) The liquidity aspect (quick ratio) 5,33% for earthenware, 1,00% for stoneware,  0,67% for castle mass, 2,00% for glazur, and 0,33% for prothotype, b) The profitability aspect (profit margin) 2,89% for earthenware,  2,31% for stoneware, 0,18% forcastle mass,  1,65% for glazur,  and 0,41% for prothotype, c) The solvability aspect (time interest earned) 1,31 times for earthenware,  1,16 times for stoneware,  0,02 times for castle mass,  0,71 times for glazur, and 0,15 times for prothotype, and d) The valuation aspect (earning peer share) Rp 707,23 for earthenware,  Rp 812,63 for stoneware,  Rp 319,12 for castle mass,  Rp 44,69 for glazur, and Rp 8,21 for prothotipe. Its contrary, the earning management can decrease activity aspect (turnover inventory) ceramics creative industry product (earthenware, stoneware, castle mass, glazur, and prothotype), these are  3,8 times,  6,47 times,  5,27 times,  8,11 times, and 11,90 times.